Determining the effect of yoga on job satisfaction and burnout of nurse academicians. Issue 1 (30th April 2021) - Kavurmaci, Mehtap; Tan, Mehtap; Bahcecioglu Turan, Gülcan
Abstract: Purpose: This study was conducted to determine the effect of yoga on burnout and job satisfaction of nursing academicians. Design and Methods: The research is an experimental clinical trial conducted as pretest–posttest with control groups between March and August 2019 in a Nursing Faculty. Participants in the experimental group were given yoga practice ( n = 33) twice a week for 8 weeks. Data were collected by using MBI and MSQ. Findings: The experimental group's mean posttest Personal Achievement, Extrinsic Satisfaction and General Satisfaction scores were higher than that of control group participants, and a highly significant difference was found between the groups. Practice implications: Yoga practice is effective in reducing the burnout and increasing job satisfaction of nursing academicians.